1997
DOI: 10.1002/(sici)1099-114x(199711)21:14<1281::aid-er322>3.3.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

PCM thermal insulation in buildings

Abstract: SUMMARYThis paper presents the results of a numerical and experimental study of phase change material (PCM) filled walls and roofs under real operational conditions to achieve passive thermal comfort. The numerical part of the study was based on a one-dimensional model for the phase change problem controlled by pure conduction. Real radiation data was used to determine the external face temperature. The numerical treatment was based upon using finite difference approximations and the ADI scheme. The results ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The daily absolute heat transfer q day , Eq. (5), has been normalized with a reference in order to facilitate the analysis q day ¼ q day q day;ref (8) q day,ref corresponds to the daily absolute heat transfer with a wall containing only an insulator (i.e., no PCM). Whenq day is lower than 1, then the PCM is useful.…”
Section: Numerical Analysis Of a Wall With One Pcm Layermentioning
confidence: 99%
See 1 more Smart Citation
“…The daily absolute heat transfer q day , Eq. (5), has been normalized with a reference in order to facilitate the analysis q day ¼ q day q day;ref (8) q day,ref corresponds to the daily absolute heat transfer with a wall containing only an insulator (i.e., no PCM). Whenq day is lower than 1, then the PCM is useful.…”
Section: Numerical Analysis Of a Wall With One Pcm Layermentioning
confidence: 99%
“…Alawashi [7] performed a thermal analysis of a wall containing cylindrical PCM intrusions, and observed a reduction in heat flow through the wall during working hours. Ismail and Castro [8] studied a room in real operating condition with PCM filled walls. Results showed that using PCM slab in walls reduced the HVAC energy consumption of 20-30% compared to a conventional wall.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, in 1997, Ismail and Castro [81] integrated PCM (a mixture of two commercial grades of glycol) as a thermal barrier in brick walls and roofs typical of Brazilian construction. Side by side experiments were performed to compare the behaviour of the new concepts with conventional ones and to validate a numerical model.…”
Section: Macro-encapsulated In Plates or Bagsmentioning
confidence: 99%
“…Ismail et al [17] presented the results of a numerical and experimental study of PCM-filled walls and roofs under real operational conditions to achieve passive thermal comfort. The numerical part of the study was based on a one-dimensional model for the phase change, controlled by pure conduction.…”
Section: Implementing Pcm In the Building Envelopementioning
confidence: 99%